Inversión económica para la compra de materiales destinados a la producción de banano en Supermag S.A, 2020. - Espinoza Morocho, Ronald Fernando; Corte Solorzano, Sleiter Yordey (Machala : Universidad Técnica de Machala, 2022)
The present investigation tries to diagnose the administrative and operative process in the entity, the investment and production control that the company uses and what are its shortcomings in the operative areas, to promote the production processes in this way to make precise decisions for the organization; due to the fact that the system that is applied to the activities at the time was not effective, which limits the company to obtain greater profitability and liquidity. Without leaving aside the phases that control the management that is applied in the company; The objective of the company is that the human and financial resources are necessary for the company, and that they are competitive in the business market, which is why a current model must be implemented to efficiently control investments and production costs; and thus, obtain optimal financial management of the organization. For this reason, in the second chapter the theoretical bases that relate to management control and its elements, the laws that support the research, and scientific articles related to management control are placed. The quantitative method is used for the investigation, surveying the members of the company, where the method is positivist because the investment and production costs are relatively positive for the organization. Still, if shortcomings were found after the results were analyzed, that the system that they use technologically need to update it, therefore the research is perspective because the object of the study is to analyze the system they use. Hence, the research is progress for the company. So that all the operational areas are very well managed and controlled, through current and necessary financial indicators for the entity. After conducting analysis and analysis with research methods, conclusions and recommendations are made to the company that must be improved and implemented in the organization.
La presente investigación trata de diagnosticar el proceso administrativo y operativo en la entidad, sobre el control de inversión y producción que utiliza la compañía y cuáles son sus falencias en las áreas operativas, potenciar los procesos de producción de esa forma tomar decisiones precisas para la organización; debido a que el sistema que es aplicado para las actividades en su momento no fue eficaz, lo que limita a la compañía a obtener una mayor rentabilidad y liquidez. Sin dejar de lado las fases que controlan la gestión que se aplican en la compañía; el objetivo de la compañía es que los recursos humanos y financieros sean necesarios para la empresa, que sean competitivos en el mercado de los negocios, es por ello que se debe implementar un modelo actual para controlar eficientemente las inversiones y costos de producción; y así obtener una óptima gestión financiera de la organización. Por tal motivo en el segundo capítulo se colocan las bases teóricas que relacionan el control de gestión y sus elementos, las leyes que avalen la investigación y artículos científicos con relación al tema de control de gestión. Se utiliza para la investigación el método cuantitativo encuestando a los miembros de la compañía, donde el método es positivista porque la inversión y los costos de producción es relativamente positivo para la organización pero si se encontró falencias después que se analizó los resultados, que el sistema que utilizan tecnológicamente necesitan actualizarlo por lo tanto la investigación es perspectiva porque el objeto del estudio es analizar el sistema que utilizan, entonces la investigación es un progreso para la compañía. Para que todas las áreas operativas sean muy bien manejadas y controladas, mediante indicadores financieros actuales y necesarios para la entidad. Después de realizar análisis y análisis con métodos de investigación, se procede a conclusiones y recomendaciones a la empresa que se deben mejorar e implementar en la organización.
Keywords: FUNDAMENTOS DE INVERSION; TIPOS DE INVERSION; PRODUCCION; COSTOS DIRECTOS